Effects of cyclic loading on the strength and characteristics of weathered granite / Ahmad Fadzil Jobli - Jobli, Ahmad Fadzil (2014)
With the use of advance GCTS Triaxial RTX-3000 machine, uniaxial cyclic loading test was conducted to describe the effects of cyclic loading on the strength and characteristics of weathered granite. In order to achieve the objectives, the behavior of cylindrical rock specimens before and after cyclic loading should be studied and some of physical and mechanical properties were analyzed. Under cyclic loading configuration, amplitude was taken as 50 % of maximum compressive strength, and the numbers of cycles were limited to 100 cycles with frequency of 1 Hertz. Based on the properties characterization, it was found that uniaxial compressive strength of granite reduced with weathering grades by 45% to 75%. It also demonstrates that uniaxial compressive strength of weathered granite can be predicted from schimdt hammer test and ultrasonic pulse velocity test. Considering the effects of cyclic loading, the maximum percentage reduction of strength for Grade II, Grade III, and Grade IV granite were recorded as 13.50 %, 15.15 %, and 16.30 % respectively. On the other hand, the elasticity and pulse velocity showed an increased value although the compressive strength was found to be decreased. Conclusively, it can be deduced that cyclic loading with amplitude of half of the static strength can reduce the strength of weathered granite up to 15 %, meanwhile the observe increase of elasticity and pulse velocity are due to the increase of bulk compressibility and accumulated permanent strain damage resulting from cyclic loading, thus reducing compressive strength of weathered granite.